Frame analysis of the 2019 trade dispute and Zainichi Koreans in South Korean newspapers - Vasileva, Natalia (My University, 2025)
The complicated relations between South Korea and Japan continue to present a “puzzle” for international relations theory. Their strategic and economic closeness suggests political closeness as well, however, that is not the case. The root cause of the repeated clashes is the so-called “history problem” – disputes and issues stemming from Japan's colonial rule of Korea (1910-1945). Opposing attitudes to this “history problem” have become a part of South Korea’s and Japan’s national identities, affecting the foreign policy decisions they employ. Such foreign policy decisions, in turn, continue to produce and reproduce the dominant national identities, presenting a mutually constitutive relationship. This study utilizes the poststructuralist approach to discursive national identity construction to explore how the trade dispute of 2019 was framed in South Korean newspapers, aiming to identify not only the dominant, but also alternative discourses, which could suggest possible solutions to the “history problem” and the ongoing clashes between South Korea and Japan. In addition, to add dimension to the study of (South) Korean national identity construction, frames of Zainichi Koreans – Korean minority in Japan – are also explored, as well as the effects of partisan leaning of the newspapers on the way they frame the issues. Through the frame analysis of 4 South Korean newspapers, it was confirmed that the dominant discourse present in media is still that of South Korea as the victim and the one remembering the past and Japan as the aggressor and the one trying to forget. As Zainichi Koreans have also faced discrimination and hardships in their lives in Japan, essentially being victims juxtaposed to Japan’s oppression, they were also framed as Koreans – “one of us” as opposed to the Japan’s “other.” However, alternative views were also identified, such as suggestions to not forget, but “overcome” the overbearing focus on the past, most prominently exhibited by the conservative Chosun Ilbo. This study argues that such discourse existing helped to make the subsequent resolution of the trade dispute possible and imaginable to the South Korean public, thus suggesting that we may see the “history problem” between South Korea and Japan resolved in the future if this alternative discourse continues to grow and develop to contest the dominant one.
Keywords: Zainichi, South Korea, Japan, national identity, history problem, trade dispute, frame analysis